Conceptual and Practical Dimensions of Problem-Based Learning in Fiqh Instruction - Syarifulanam Cahyadika; Nurul Latifatul Inayati (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2025)
Fiqh learning in many Indonesian madrasahs continues to rely heavily on teacher-centered methods, resulting in limited student participation and low problem-solving ability despite national data indicating that 62% of junior secondary students fall into the low category in analytical competencies. This study addresses the persistent gap between the theoretical objectives of Fiqh as an applied discipline and the predominance of lecture-based instruction at MTs Muhammadiyah Blimbing, where preliminary observations revealed that only 22% of students were able to apply Fiqh rulings to real-life cases. The research aims to analyze the conceptual alignment and practical implementation of the Problem-Based Learning model, with particular attention to its planning, classroom enactment, and evaluation processes. Using a qualitative field research design, data were collected through classroom observations, in-depth interviews with the Fiqh teacher, and documentation analysis. Findings show that PBL was systematically planned through the preparation of contextual problem worksheets, structured group arrangements, and lesson plans aligned with PBL principles. Classroom implementation demonstrated increased student engagement, with students actively identifying problems, locating textual evidence, and discussing solutions, although participation remained uneven across groups. The evaluation phase combined process-based and summative assessments, revealing strong cognitive mastery but variable argumentation quality. Overall, PBL contributed positively to contextualizing Fiqh concepts and strengthening students’ analytical competence, indicating the need for enhanced scaffolding strategies, improved assessment design, and institutional support to ensure more equitable learning outcomes.